2021
DOI: 10.1108/medar-05-2020-0901
|View full text |Cite
|
Sign up to set email alerts
|

Implications of recent reforms to auditor reporting requirements in Australia

Abstract: Purpose This paper aims to address a topical and controversial issue, namely, the degree of conformity with the new auditor reporting requirements in Australia and the extent of variations in the reporting of key audit matters (KAMs) by Australian firms. Design/methodology/approach This paper compares the 64 elements identified in the applicable standards with the auditor’s report from the sampled companies to determine the degree to which the top 200 firms listed on the Australian Stock Exchange are complyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 38 publications
(48 reference statements)
1
12
0
Order By: Relevance
“…Australia, The Netherlands, Egypt, Oman and Jordan) and explored its various aspects, including its acceptance rate from the stockholders’ (e.g. auditors and managers) points of view (Rahaman and Chand, 2022; Kend and Nguyen, 2020; Woudenberg et al , 2021; Hegazy and Kamareldawla, 2021; Baatwah, 2022; Abdullatif and Al‐Rahahleh, 2020).…”
Section: Results Of Content Analysismentioning
confidence: 99%
“…Australia, The Netherlands, Egypt, Oman and Jordan) and explored its various aspects, including its acceptance rate from the stockholders’ (e.g. auditors and managers) points of view (Rahaman and Chand, 2022; Kend and Nguyen, 2020; Woudenberg et al , 2021; Hegazy and Kamareldawla, 2021; Baatwah, 2022; Abdullatif and Al‐Rahahleh, 2020).…”
Section: Results Of Content Analysismentioning
confidence: 99%
“…Users of financial statements might perceive the auditor's disclosure of KAMs as inconsistent and biased, especially when compared with the issuance of a clean audit report on the same financial statements (Coram & Wang, 2020). This inconsistency can impact users' investment decisions, leading to a loss of confidence in the auditor's reports and fostering the perception of conflicting opinions (Rahaman & Chand, 2022). Additionally, an increase in the auditor-disclosed KAM poses a potential threat to financial statement users, diverting their attention from other critical sections of the auditor's reports (Li et al, 2019;Sirois et al, 2018).…”
Section: Expected Opportunities and Challenges Of Key Audit Matter Di...mentioning
confidence: 99%
“…Later, it will be followed by a segment of the effects of disclosure (Li, Hay, & Lau, 2019;Segal, 2019;Velte, 2020;Kitiwong & Sarapaivanich, 2020;Rautiainen, Jani, & Kati, 2021). In the last segment, this paper will discuss the KAM's reporting mechanism (Rahaman & Chand, 2021;Mihret, Kansal, Muttakin, & Rana, 2022;Wuttichindanon & Issarawornrawanich, 2020).…”
Section: Key Audit Matters (Kam)mentioning
confidence: 99%
“…However, the requirement for the KAM does not affect the Big 4 companies, and it is just one step extra in reporting the audit procedures (Nguyen & Kend, 2021). Another study found vast differences in the reporting style between new auditor reports and experience auditors (Rahaman & Chand, 2021). Another study further explained that the experience auditors improved the reporting style from year to year (Nguyen & Kend, 2021).…”
Section: Factors That Influence Kammentioning
confidence: 99%